PREVALENCE AND CHARACTERIZATION OF VIRULENCE GENES OF ESCHERICHIA COLI IN DIABETIC AND NON-DIABETIC URINARY TRACT INFECTED PATIENTS USING MULTIPLEX PCR TECHNIQUE - R. PADMINI,; . PANNEERSELVAM, (The Bioscan, 2012)
The present study was designed to characterize virulence genes of Escherichia coli in diabetic and non-diabetic urinary tract infected (UTI) patients. About 299 urine samples were collected from diabetic and non-diabetic patients from Gopi Hospital, Salem. Among them, 30 isolates were found positive and 10 isolates were subjected to Multiplex PCR technique for the detection of fim H (type 1 fimbriae) gene, pap E/F (minor structural subunits of P fimbriae) gene and cnf-1 (cytotoxic necrotizing factor type-1) gene. The study concludes the presence of E.coli in UTI patients and shows antimicrobial susceptible pattern of isolated E.coli. The identification of fim H and pap E/F genes and also attempts to generate a vaccine against uropathogenic E. coli.